ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RISK BASED BANK RATING (Studi Kasus Pada PT. Bank Jatim Tbk) - Ariyanti, Destya Dwi (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to analyze the soundness of PT. Bank Jatim Tbk during the period of 2013 to 2016 using Risk Based Bank Rating method in accordance with the letter of Bank Indonesia No. 13/24/DPNP on October 23, 2011 which is described by RGEC aspects which consists of Risk, Good Corporate Governance (GCG), Earnings, and Capital. This quantitative descriptive research calculates the ratios in risk aspects (NPL, LDR, and LFR), earnings (ROA and NIM), capital (CAR), and analyze self assesment results of GCG. This research uses secondary data in forms of documentation of Bank Jatim’s annual report publication during the period of 2013 until 2016, when Bank Jatim have used IPO system (Initial Public Offering) for a full year. The data were obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The results show that in general Bank Jatim during the research period of 2013 to 2016, is categorized as a healthy bank. This is evident from the fact that all calculated ratios meet the criteria set by Bank Indonesia. The Bank reached the composite of one or highest healthy level and three or healthy enough for the lowest healthy level.Keywords : Bank soundness, Regional Development Bank, Risk-Based Bank Rating, Bank Jatim